2017
DOI: 10.1590/1678-4162-8373
|View full text |Cite
|
Sign up to set email alerts
|

Dermatite piogranulomatosa ulcerativa em bovino por Corynebacterium pseudotuberculosis

Abstract: RESUMORelata-se um caso de lesão cutânea secundária à infecção por Corynebacterium pseudotuberculosis em bovino. Abscessos e múltiplas lesões cutâneas nodulares, variando de 8x10 para 20x25cm de diâmetro, firmes, sensíveis ao toque e sem mobilidade, algumas com superfície ulcerada, circundada por halo avermelhado e drenando secreção piossanguinolenta, e outras com superfícies alopécicas, foram identificados na região torácica lateral do animal. Exames histopatológicos e o isolamento do agente de fragmentos obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These findings demonstrated that these diseases are important in the region, mainly because the most common were infectious and inflammatory diseases, representing more than half of the cases of skin diseases (54.7%). In Brazil, there is little information on the prevalence of skin diseases in cattle, with reports of only specific diseases and isolated outbreaks (Gabriel et al 2008, Leal et al 2017, Reis et al 2017, Soares et al 2017, Mendonça et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings demonstrated that these diseases are important in the region, mainly because the most common were infectious and inflammatory diseases, representing more than half of the cases of skin diseases (54.7%). In Brazil, there is little information on the prevalence of skin diseases in cattle, with reports of only specific diseases and isolated outbreaks (Gabriel et al 2008, Leal et al 2017, Reis et al 2017, Soares et al 2017, Mendonça et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These skin diseases can have different etiologies and among them are those related to nutritional problems (Hensel 2010), infectious agents (Motta et al 2010, Foster 2012, Panziera et al 2016, Soares et al 2017, Bertagnolli et al 2020, Pereira & Meirelles 2023a, neoplasms (Reis et al 2017), those associated with allergic processes (Dutra 1998, Santos et al 2021, Schild 2023) and those caused by the action of toxic agents (Knupp et al 2016, Santos et al 2017, Amado et al 2018, Mendonça et al 2021.…”
Section: Introductionmentioning
confidence: 99%